A New Approach to Evaluate the Effectiveness of Rockfall Barriers. (2016) - Mentani, Alessio; Govoni, Laura; Gottardi, Guido; Lambert, Stéphane; Bourrier, Franck; Toe, David
Abstract: The paper addresses the response of a semi-rigid rockfall protection barrier using numerical models. The study show a large dependence of the barrier response to the impact conditions. The block size and impact position, rather than the velocity direction and magnitude induce different modes of failure of the fence, which in turn result in different values of failure energy. As a result, the barrier capacity cannot be established in a deterministic way. The effectiveness of structures as such can be more successfully evaluated through a reliability probabilistic approach. Results can be used to create a meta-model of the barrier response which can be incorporated into rockfall simulation models, enabling a reliable and comprehensive design of rockfall mitigation interventions performed with this type of structure.